A new species of the genus Oligodon Fitzinger, 1826 (Squamata: Colubridae) from Pulau Nias, Indonesia - David, Patrick; Vogel, Gernot (Zootaxa, 2012)
A new species of the genus Oligodon Fitzinger, 1826, Oligodon wagneri sp. nov., is described on the basis of a singlespecimen originating from Nias Island, off the west coast of Sumatra, Indonesia. It differs from other species of the regionby the combination of a constant number (15) of dorsal scale rows, undivided hemipenes, entire anal plate, form of den-tition, and dorsal pattern of white crossbars alternating with three irregular reticulations. This new species is comparedwith other species of the Greater Sunda Islands with 15 or 17 dorsal scale rows. An updated checklist and key to Oligodon species of the region of Sumatra is provided.